2015
DOI: 10.1097/01.ogx.0000471594.65931.90
|View full text |Cite
|
Sign up to set email alerts
|

Copy Number Variations and Cognitive Phenotypes in Unselected Populations

Abstract: In the human genome, genetic sequences that differ in the numbers of copies, or so-called copy number variations (CNVs), can be associated with intellectual disability and developmental delay. Large, recurrent CNVs are particularly associated with these complex disorders. Previous studies of the effects of large CNVs have generally pediatric subjects with clinical disordered, and there are more limited data on the population frequency in asymptomatic adults. This study looks at the adult carriers of CNVs and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
76
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(90 citation statements)
references
References 0 publications
11
76
1
2
Order By: Relevance
“…In this issue of JAMA , Männik and colleagues 1 report that large (>250 kilobase [kb] pairs) structural variants in the genome, specifically deletion and duplication copy number variations (CNVs), were associated with cognitive phenotypes including intellectual disability and reduced educational achievement. These CNVs are deletions and duplications of DNA sequences in the human genome that can be considered as deviations from the normal diploid state at a given location in the genome and represent differing numbers of copies of genetic sequences.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of JAMA , Männik and colleagues 1 report that large (>250 kilobase [kb] pairs) structural variants in the genome, specifically deletion and duplication copy number variations (CNVs), were associated with cognitive phenotypes including intellectual disability and reduced educational achievement. These CNVs are deletions and duplications of DNA sequences in the human genome that can be considered as deviations from the normal diploid state at a given location in the genome and represent differing numbers of copies of genetic sequences.…”
mentioning
confidence: 99%
“…The investigators identified 56 carriers of CNVs associated with known genomic disorders, previously cataloged in the Database of Chromosomal Imbalance and Phenotype in Humans Using Ensembl Resources (DECIPHER) 4 within a combined discovery and replication sample of 7877 unrelated individuals, which repre sented a rate of 7.1 per 1000 personal genomes assayed, or approximately 1 in every 141 individuals studied. 1 …”
mentioning
confidence: 99%
“…This model is supported by studies in individuals who have the common 15q11.2 deletion ascertained from the general population, who have been found to have lower functioning on neuropsychological measures compared to population controls . More generally, in the population, the presence of larger CNVs has been shown to be associated with lower educational achievement in the absence of a diagnosed neurodevelopmental disorder …”
Section: First‐tier Genetic Investigations: Chromosome Microarray Andmentioning
confidence: 99%
“…This is supported by recent studies of general populations that showed negative effects of such CNVs, including cognitive impairments, other neuropsychiatric features, alterations in body weight, and reduced fecundity. 72,73 Therefore, it is likely that most of these CNVs have some type of negative impact on an individual's development and neurologic function, although these impacts may not always be sufficient to bring the individual to clinical attention. Fig.…”
Section: Discovery Of Microdeletion and Microduplication Syndromesmentioning
confidence: 99%